Less is more: The physiological basis for tapering in endurance, strength, and power athletes - Murach, K. A.; Bagley, J. R. (Sports, 2015)
Taper, or reduced-volume training, improves competition performance across a broad spectrum of exercise modes and populations. This article aims to highlight the physiological mechanisms, namely in skeletal muscle, by which taper improves performance and provide a practical literature-based rationale for implementing taper in varied athletic disciplines. Special attention will be paid to strength- and power-oriented athletes as taper is under-studied and often overlooked in these populations. Tapering can best be summarized by the adage "less is more" because maintained intensity and reduced volume prior to competition yields significant performance benefits.